Justice delayed is justice denied?: divorce case management in Malaysian shariah court - Ismail, S.Z.; Abdul Ghani Azmi, I.; Yasoa, Z. (2011)
One of the problems that influence the quality of administering justice is the duration of court proceeding. This problem has been significantly recognized in many countries. In Malaysia, the lengthy duration of court proceedings pertaining to divorce cases of Muslim couples is particularly considered to be a problem in Malaysian shariah court. In fact, this is the most prevalent complaint ever lodged by the public to Shariah Judiciary Department (JKSM) every year. While it is true that delay indicates inefficiency in management, the interpretive standard used by the JKSM concerning delay is applied for cases which reach settlement after 360 days. Therefore, what is deemed to be delay by laymen, is perhaps not so by the shariah court’s standard. There are still far lack of empirical and extensive academic studies on divorce case management especially concerning delay in case settlement. The objective of this research is to examine whether delay exists in case management in Shariah court, how extensive and critical it is by looking at the contributing factors. Dissolution of marriage cases are chosen as the sample of the study as these cases are frequently bogged with delays.